Molecular Recognisation of 3a, 4-Dihydro-3-H-Indeno [1, 2-C] Pyrazole-2- Carboxamide/Carbothioamide Anticonvulsant Analogues Towards GABA-Aminotransferase- An in Silico Approach - Mathew, Bijo; J. Ahsan, Mohamed (Central Nervous System Agents in Medicinal Chemistry, 2014)
Convulsion generally occurs as a result of the diminishing concentration of GABA below a threshold level in the brain. This degradation pathway of GABA is catalyzed by the γ-aminobutyric acid amino transferase. The objective of the current study is to propose the binding interaction of 3a, 4-Dihydro-3-H-indeno [1, 2-C] pyrazole-2-Carboxamide/ Carbothioamides anticonvulsant analogs with a three-dimensional structural model of the γ -aminobutyric acid amino transferase. For a flexible type of molecular docking, we proposed that these molecules could successfully bind to the active pocket of the enzyme with good predicted affinities in comparison to standard vigabatrin. In this series, 4b, 4c, 4i, 4f and 4a showed significant binding free energy of -9.64, -9.31, -9.01, -8.99 and -8.29 with predicted inhibitory constant values of 0.086, 0.149, 0.237, 0.257 and 0.831 µM, respectively.
Keywords: GABA-AT